Front Cover: Development of Highly Selective Support for CO Hydrogenation to Light Olefins with Partially Passivated Iron Catalysts (ChemCatChem 14/2019). Issue 14 (18th July 2019) - Xing, Yu; Jia, Gaopeng; Liu, Zhenxin; Fang, Shaoming; Zhao, Chenxi; Guo, Xuehui; Suib, Steven L.
Abstract : The Front Cover shows that light olefins (ethylene, propylene and butylene) may be selectively generated through conversion of syngas over an iron catalyst with a partially passivated Al–O–Zn support. In their Full Paper, Yu Xing et al. demonstrate that a 1200 °C passivated solid base composite, ZnAl2 O4 ⋅3Al2 O3 was the most selective support material for iron‐based Fischer‐Tropsch to light olefins (FTO) catalysts, of which the C2 = ‐C4 = hydrocarbon distribution increased by almost 100 % in comparison with Fe catalysts on regular supports. More information can be found in the Full Paper by Yu Xing et al. onpage 3187 in Issue 14, 2019 (DOI:10.1002/cctc.201900023 ).